Hubungan Pengetahuan dan Jumlah Pasangan Seksual dengan Risiko HIV pada Wanita Pekerja Seksual (WPS) di Kota Ternate - Nita Anggerina Putri Hi Setiawan; Dwi Sutiningsih; Bagoes Widjanarko (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: The number of HIV/AIDS cases in Ternate is increasing, until now there are 472 cases reported and in 2019 there were 46 new cases. FSW is one of the key population at risk of HIV.Methods: The purpose of this study was to identify the correlation between knowledge and number of sexual partner with HIV risk among female sex workers (FSW) in Ternate. This study used a cross sectional design. The number of respondents was 92 respondents. The instrument used in this study was a questionnaire. Data analysis was univariate, and bivariate with chi-square.Result: There were correlation between knowledge (p= 0,013; PR 1,363; 95% CI 1,069-1,704), and the number of sexual partners (p= 0.030; PR 1,497; 95% CI 0,961-2,331) with HIV risk among FSW in Ternate.Conclusion : FSW who had poor knowledge and had ≥3 clients, was correlated with HIV risk.